Upscaling of a double porosity problem with jumps in thin porous media. Issue 9 (13th June 2022) - Bunoiu, Renata; Timofte, Claudia
ABSTRACT: We study the homogenization of a double porosity diffusion problem in a thin highly heterogeneous composite medium formed by two materials separated by an imperfect interface, where the solution and its flux exhibit jumps. By applying homogenization techniques specific to the thin periodic domain under study, one derives the limit problem.